Analysis of rice characteristic volatiles and their influence on rice aroma - Shuimei Li; Hongyan Li; Lin Lu; Gaoneng Shao; Zhenling Guo; Yuntao He; Yong Wang; Xiaohui Yang; Mingxue Chen; Xianqiao Hu (Current Research in Food Science, 2024)
Rice aroma, one of the most important qualities of rice, was the comprehensive result of volatiles in rice and human sense. In this study, the main volatile compounds in rice were analyzed by using gas chromatography-mass spectrometry and gas chromatography-olfactometry, and their correlations with sensory score were investigated. A total of eighty-five volatiles were found in rice samples. By combining odor activity value and correlation analysis, nine volatiles were considered as potential characteristic volatiles in rice aroma, namely hexanal, 2-pentylfuran, octanal, 2-acetyl-1-pyrroline (2-AP), 1-octen-3-ol, trans-2-octenal, decanal, trans-2-nonenal and trans, trans-2,4-decadienal. It was found that the volatiles negatively correlated with sensory scores were positively correlated with hexanal. It indicated that hexanal might be a representative of the negative volatiles of rice aroma. The effects of the nine potential characteristic volatiles on rice aroma were investigated by using sensory analysis. The results showed that the odor intensity and preference level of 2-AP, hexanal, and 1-octen-3-ol were significantly affected by the content. Furthermore, the aroma of cooked rice was significantly different after adding 2-AP, hexanal or trans, trans-2,4-decadienal. Rice aroma was increased by adding 2-AP and deteriorated by adding hexanal or trans, trans-2,4-decadienal, indicating that 2-AP contributed positively to rice aroma while hexanal and trans, trans-2,4-decadienal contributed negatively to rice aroma. Hexanal, 2-AP, and trans, trans-2,4-decadienal were suggested to be the key characteristic volatiles for future aroma evaluation.